Growth Characteristics of Vetiver Grass (Vetiveria zizanioides) on Saline Soils - Aisar Novita; Merlyn Mariana; Silvia Nora; Elrisa Ramadhani; Hilda Julia; Anggria Lestami (Universitas Panji Sakti, 2022)
Vetiver is widespread in saline areas. Only a few studies have reported that they are sufficiently tolerant of salt. The primary mechanism of salt tolerance in vetiver is still not known with certainty. This study aims to determine salinity's effect on early growth of vetiver (Vetiveria zizanioides L.) seedlings. This research was conducted in a greenhouse, Faculty of Agriculture, Universitas Sumatera Utara, Medan. This study used a non-factorial randomized block design (RBD), namely the salinity stress (S) which consisted of 3 levels: EC salinity levels of 0 (distilled water), 4 dsm-1 and 8 dsm-1. The salinity stress treatment showed a significant effect of reducing the growth parameters of plant height, leaf area, chlorophyll a and chlorophyll b. Salinity stress treatment gave significantly better effect in conditions without salinity stress.